O amor on-line e sua função para uma adolescente : uma versão contemporânea do amor cortês? - Allana Fernanda Gonçalves Dias (2024)
This research, based on a clinical case of an adolescent girl who experienced a long-term romantic bond with another adolescent girl through social media, aims to identify the function of this love bond: does it serve as a support for constructing the fantasy of complementarity between sexes for the teenager? The case led us to formulate a second question: is this love a contemporary manifestation of courtly love in the virtual space? Using the psychoanalytic method, the clinical vignette allows us to go beyond the case, questioning the conditions of our era influenced by digital culture within the context of adolescence. The contemporary period is marked by specificities that hinder the construction of fantasy. On one hand, there is the lifting of the veil in an era emptied of ideals. On the other, haste and urgency modify the ways of connecting with others. In this context, the virtual scenario offers conducive conditions for the liquidity of love, as connections and disconnections occur at an increasing speed in this space. The search for a partner in the digital realm is influenced by capital, thus taking the form of an economic transaction regulated by supply and demand. This discourse imposes a decline in fantasy and an acceleration of time. Courtly love opposes this logic by enabling the creation of a veil and a dilation of time, facilitating the necessary conditions for fantasy construction. The virtual space provides a favorable setting for individuals to maintain a distant, unattainable, and idealized love. We conclude that online love, in addition to operating as a support for the construction of fantasy in the first logical period of adolescence, represents a contemporary version of courtly love for a teenager. Thus, despite love appearing to decline in our time, it has been possible to observe that aspects of an "ideal of love" can still be preserved among young people.